2014
DOI: 10.1007/978-3-662-44426-9_20
|View full text |Cite
|
Sign up to set email alerts
|

Categorization of Brazilian Internet Users and Its Impacts on the Use of Electronic Government Services

Abstract: This paper aims to categorize Brazilian Internet users according to the diversity of their online activities and to assess the propensity of these Internet users´ groups to use electronic government (e-gov) services. The Amartya Sen's Capability Approach was adopted as the theoretical framework for its consideration of people's freedom to decide on their use of available resources and their competencies for these decisions, leading to the use of e-gov services. Multivariate statistical techniques were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Given the heterogeneous Internet access throughout Brazil, we analyzed the role that accessibility could play in explaining our ability to track dengue incidence via GHT. Since 2005, Brazil has monitored the accessibility of their population to information and communication technologies [59,60] [61]). We analyzed data from the 2015 survey, which included a sample of 356,904 individuals and 151,189 households distributed across the country and was subsequently extrapolated to a total of 177,657 million people and 68, 037 million households [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Given the heterogeneous Internet access throughout Brazil, we analyzed the role that accessibility could play in explaining our ability to track dengue incidence via GHT. Since 2005, Brazil has monitored the accessibility of their population to information and communication technologies [59,60] [61]). We analyzed data from the 2015 survey, which included a sample of 356,904 individuals and 151,189 households distributed across the country and was subsequently extrapolated to a total of 177,657 million people and 68, 037 million households [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…A crucial concern of this study was to assess whether the tool accessibility would be similar, in the context of the social diversity that is found in Brazil (Araujo and Reinhard, 2016; UNESCO, 2019). Despite socioeconomic differences, the results obtained have shown that most of the students had access to the Internet and computers outside the RPMS campus.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, Brazil has experienced a rapid increase in the number of private medical schools, with considerable discrepancies in teaching‐learning methods and quality‐standard maintenance between public and private schools, as assessed by the National Examination of Students' Performance (ENADE) (Scheffer and Dal Poz, 2015; Antunes Dos Santos and Nunes, 2019). In addition, Brazil maintains immense socioeconomic inequalities that reflect upon the households with Internet access: extremely high in the upper social classes (A and B) and much lower in C, D, and E social classes (Araujo and Reinhard, 2016; UNESCO, 2019). Therefore, in developing countries, such as Brazil, online laboratory platforms are still in the process of implementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the individual level, the e-government literature discusses indicators of a person's general inclination to surf the internet, her equipment with modern internet access appliances and her overall computer literacy as facets of an individual's general internet-related experience level, which may explain differences in the use intensity of e-government services between individuals. Most earlier work found that these facets are significantly positively associated with the use level of e-government services (Anduiza et al, 2010;de Araujo and Reinhard, 2014;Azam et al, 2013;Bélanger and Carter, 2009;Colesca and Dobrica, 2008;Fu et al, 2006;Hansen and Reinau, 2006;Nam, 2014;Reddick, 2005;Taipale, 2013;Van Dijk et al, 2008;Van Dijk et al, 2007;Voutinioti, 2013;Wang, 2002;Zhao and Khan, 2013;Zheng, 2015). Thus, we test the following three propositions:…”
Section: Research Hypothesesmentioning
confidence: 94%